Tangled - Greno, Nathan; Howard, Byron; Moore, Mandy, 1984-; Levi, Zachary, 1980-; Murphy, Donna; Garrett, Brad, 1960-; Perlman, Ron, 1950-; Tambor, Jeffrey, 1944-; Grimm, Jacob, 1785-1863.; Grimm, Wilhelm, 1786-1859.; Walt Disney Pictures; Walt Disney Studios Home Entertainment (Firm); et al. ([United States] : Walt Disney Studios Home Entertainment ; Burbank, Calif.. : Distributed by Buena Vista Home Entertainment, 2011)
When the kingdom's most wanted bandit Flynn Rider hides in a mysterious tower, the last thing he expects to find is Rapunzel, a spirited teen with an unlikely superpower, 70 feet of magical golden hair! Together, the unlikely duo sets off on a fantastic journey filled with surprising heroes, laughter, and suspense.
Based on the story "Rapunzel" by Jacob Grimm and Wilhelm Grimm.
Originally released as a motion picture in 2010.
Special features: two original storybook openings and an animated countdown.
Voices: Brad Garrett, Jeffrey Tambor, Ron Perlman, Zachary Levi, Donna Murphy, Mandy Moore.
Rating: PG; for brief mild violence.
DVD; widescreen (1.78:1); NTSC, region 1; Dolby Digital 5.1 surround sound.
Keywords: Rapunzel (Tale) -- Adaptations -- Juvenile drama; Princesses -- Juvenile drama; Outlaws -- Juvenile drama; Magic -- Juvenile drama; Animated films; Children's films; Feature films; Films for the hearing impaired